2009
DOI: 10.1080/02841850802524493
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous retrieval of dislodged central venous port catheter: experience of 25 patients in a single institute

Abstract: Although the prevalence of port catheter dislodgement is low, percutaneous attempts at retrieval should be performed in all patients, even in chronic settings. A loop snare is the instrument of choice for retrieval. Grasping forceps can be used as an auxiliary instrument, especially in patients where a loop snare fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Although rare, Fisher and Ferreyro reported a 71% incidence of death or serious complications, such as arrhythmia, perforation, clotting, and infections. Therefore, percutaneous retrieval of the dislodged fragment should be made no matter for how long the port catheter has been dislodged [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rare, Fisher and Ferreyro reported a 71% incidence of death or serious complications, such as arrhythmia, perforation, clotting, and infections. Therefore, percutaneous retrieval of the dislodged fragment should be made no matter for how long the port catheter has been dislodged [4].…”
Section: Discussionmentioning
confidence: 99%
“…Several devices are available to retrieve a dislodged catheter, including loop snare, basket, grasping forceps, and balloon catheter [3e7]. If there is no accessible free end for retrieval, a pigtail catheter is used to relocate the dislodged port catheter followed by loop snare retrieval [3,4,7,8]. However, if the operator can use the pigtail catheter to relocate the dislodged port catheter, release an accessible free end, and grasp the pigtail catheter, at this point, a snare loop catheter can easily snare the free end of the dislodged catheter, and then the whole system can be pulled out.…”
Section: Introductionmentioning
confidence: 99%
“…In modern practice, a variety of commercially available devices (loop snare, grasping forceps, basket, deflecting wires, and balloon catheters) have been used for percutaneous retrieval of intravascular foreign bodies. Among them, the most popular device is the gooseneck loop snare; the basket is the second most commonly used tool for this purpose (22)(23)(24). When there are no free ends of the catheter accessible, multipurpose catheters can be used to reposition the fragment to the optimal site.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009 Cheng and associates published a study on the treatment of 92 dislocated port catheter fragments [11]. Likewise, Wang et al investigated 25 port catheter fragments, and determined a dislocation rate of 0.4 %, based on the total number of implanted port catheters [12]. In their study of port system complications, Vandoni et al demonstrated that rupture of the port system occurred in 5.7 % of cases.…”
mentioning
confidence: 99%
“…Temporary ventricular tachycardia was reported in one case; tricuspid valve insufficiency occurred in another -the patient complained of strong chest pains during the intervention [11]. Out of 25 cases, Wang et al described four events of brief and self-limiting arrhythmias [12]. Egglin et al recorded an arterial spasm in 6.3 % of cases; with the same frequency the foreign body could be guided only as far as the femoral vein, thus requiring surgical removal [17].…”
mentioning
confidence: 99%